Assessing regional economy in North Korea using nighttime light - Dawool Kim (Asia and the Global Economy, 2022)
North Korea is one of the most restrictive countries in terms of data accessibility, especially at the regional level. This research assesses the regional economy in North Korea using the nighttime light data. It estimates GRDP per capita at the county level in 2012–2020, the Kim Jong-Un era, and assesses the inequality of North Korean regions. The results reveal that cities such as Sinuiju have a comparable level of GRDP per capita with Pyongyang and that the spatial distribution of low-income counties changes from regions near South Korean borders to regions near Chinese borders as sanctions are implemented. Also, it appears that substantial county-level inequality exists. It calls for a need for the county-level economic research of North Korea despite the lack of regional data.